The proteomic study of sodium butyrate antiproliferative/cytodifferentiation effects on K562 cells - Grebenová, Dana; Kuzelová, Katerina; Pluskalová, Michaela; Peslová, Gabriela; Halada, Petr; Hrkal, Zbynek (Blood cells, molecules & diseases, 2006)
Employing methods of cell biology and proteome analysis tools, we examined effects of an inhibitor of histone deacetylases, sodium butyrate (SB), on the proliferation/differentiation characteristics of chronic myelogenous leukemia (CML)-derived cells K562. SB suppressed proliferation of K562 cells by inducing cell cycle arrest in G1 phase, which was followed by their transition to G0 phase (decrease of Ki-67 antigen-positive cells) and erythroid differentiation (increased glycophorin A expression and synthesis of hemoglobins). Neither terminal apoptosis (low counts of TUNEL-positive cells) nor necrosis (moderate counts of propidium iodide-positive cells) occurred. Importantly, SB attenuated protein expression of CML-related chimeric kinase BCR-ABL that is responsible for the deregulated proliferation of CML cells. The proteomic analysis (2-D electrophoresis combined with MALDI-TOF mass spectrometry and/or Western blotting) revealed several proteins that were differentially expressed or their mobility was altered due to butyrate treatment, namely, HSP90, HSP70, p23, cyclophilin A (CYPA), prefoldin2 (PFD2) and alpha-, gamma-, epsilon-human globin chains. Perturbation of HSP90 multichaperone complex of which BCR-ABL is the client protein is presumably a cause of BCR-ABL suppression. Changes in other proteins with chaperonic functions, CYPA and PFD2, may reflect SB antiproliferative and cytodifferentiation effects.
Keywords: Butyrates; Gene Expression Regulation, Leukemic; proliferace buněk; buňky K562; G1 Phase; Proteomics; Proteome; buněčná diferenciace; proteom; Cell Differentiation; butyráty; proteomika; Cell Proliferation; Humans; K562 Cells; G1 fáze; regulace genové exprese u leukemie; lidé